PQM-1 controls hypoxic survival via regulation of lipid metabolism - Thomas Heimbucher; Julian Hog; Piyush Gupta; Coleen T. Murphy (Nature Communications, 2020)
Animals respond to hypoxic stress by adjusting metabolic processes to balance survival and reproduction. Here the authors identify the transcription factor PQM-1 as a metabolic regulator that balances hypoxic lipid and carbohydrate metabolism in C. elegans to limit somatic integrity and promote progeny survival.